If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3(2x + 8) + 6x = 0 Reorder the terms: -3(8 + 2x) + 6x = 0 (8 * -3 + 2x * -3) + 6x = 0 (-24 + -6x) + 6x = 0 Combine like terms: -6x + 6x = 0 -24 + 0 = 0 -24 = 0 Solving -24 = 0 Couldn't find a variable to solve for. This equation is invalid, the left and right sides are not equal, therefore there is no solution.
| B-a/x | | 7y+9=Yt-6 | | h-18= | | -7(w-4)+3w-27=0 | | 16v^2+17v-45=0 | | 3w+4-w=5w+7-m | | 5m+4=4m | | -5(w-9)+8w+2= | | 2x^2-16x+29=0 | | -4x-7=-43 | | -6x-2=x-23 | | 5.3x+2=12.7-2 | | 7x/10=5 | | 3x-2/7=5/6 | | 6x-40=45 | | -6(4p+3)-49=5(2p+7) | | 4x^2=-24-20x | | 4.2x+31.5=-65.1 | | -86=4+10x | | 3.9x-13=1.7x+31 | | w^2+4w-124=0 | | 5/9(k-273.15) | | p=9+1.5(3) | | d/4-5 | | 3x+3x+4x=5 | | p=9+1.5(1) | | 3x+3x+4x/10=5 | | 7.2x-60=3.6x+30 | | x+4=-18 | | 6-14b=22 | | 2.3x+75.5=8.8x-22 | | 3-4x=-7-4s |